What law for transnational legal education? A cooperative view of an introductory course to transnational law and governance. (3rd April 2015) - Arjona, César; Anderson, Joshua; Meier, François; Robart, Sierra
Abstract : In this article, one professor and three students coming from four different jurisdictions reflect jointly on a singular educational experience in transnational law that took place at the Center for Transnational Legal Studies in London during the fall term of 2013. After a brief introduction to the concept of transnational law and the academic controversy surrounding it, the piece follows with a description of this unique educational experience, including the content and structure of the course, the composition of the class, the institutional environment, and the results achieved. In the more substantial part of the paper, the co-authors investigate several conclusions and lessons learned from the experience. The article argues against the alleged obscurity of the concept of transnational law itself, but rather roots the problems of transnational legal education in the methodological challenges it poses, the confusion of descriptive and ideological claims, and finally in different expectations about the pedagogical goals transnational education should achieve.